If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -1(5 + -2x) = 2(8 + -3x) + -1(2 + -7x) + -5 12 + (5 * -1 + -2x * -1) = 2(8 + -3x) + -1(2 + -7x) + -5 12 + (-5 + 2x) = 2(8 + -3x) + -1(2 + -7x) + -5 Combine like terms: 12 + -5 = 7 7 + 2x = 2(8 + -3x) + -1(2 + -7x) + -5 7 + 2x = (8 * 2 + -3x * 2) + -1(2 + -7x) + -5 7 + 2x = (16 + -6x) + -1(2 + -7x) + -5 7 + 2x = 16 + -6x + (2 * -1 + -7x * -1) + -5 7 + 2x = 16 + -6x + (-2 + 7x) + -5 Reorder the terms: 7 + 2x = 16 + -2 + -5 + -6x + 7x Combine like terms: 16 + -2 = 14 7 + 2x = 14 + -5 + -6x + 7x Combine like terms: 14 + -5 = 9 7 + 2x = 9 + -6x + 7x Combine like terms: -6x + 7x = 1x 7 + 2x = 9 + 1x Solving 7 + 2x = 9 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + 2x + -1x = 9 + 1x + -1x Combine like terms: 2x + -1x = 1x 7 + 1x = 9 + 1x + -1x Combine like terms: 1x + -1x = 0 7 + 1x = 9 + 0 7 + 1x = 9 Add '-7' to each side of the equation. 7 + -7 + 1x = 9 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 9 + -7 1x = 9 + -7 Combine like terms: 9 + -7 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| (3x-2)(x+3)=55 | | (3x-2)(x+3)=20 | | 3+6M=12+3M | | 2x-13=5x-52 | | 16x-54=3x+24 | | bmi=w/h^2*703 | | 9(22+5)=243 | | 12x^2-104x+96=0 | | 247.20=8(0.06m+21.80+0.20(21.80)) | | 247.20=8(0.06+21.80+0.20(21.80)) | | 2x-x^2=0.5 | | 13x-17=4x-80 | | -7.2(x-2.25)=21.6 | | 0=4*8x+4 | | 0=4*8x | | 3.2=4/5(b-3) | | 13x-123=59 | | 0=1.2+6.6*x+0.5*9.82*x^2 | | 33(p+30)=3168 | | 33(p+30)=33 | | 3230=38(p+15) | | x+4+y=0 | | 5x+25=-40 | | 168x-143=361 | | 2x-1=-y | | 13x=96+7x | | (6-3b)(6-b)(6+b)(6+3b)=945 | | 3w^2+6w-24=0 | | 6x-51=3 | | 26=-2(10+x) | | 1/18÷1/9×5/2 | | 5(x)+(3)=93 |